(untitled) (Research, Society and Development, 2020)
It is an integrative review that aimed to learn about the nutritional profile and lifestyle of elderly people who attend universities for the elderly. In this sense, a search was carried out in the databases Scielo, VHL, CAPES Periodical Portal, by crossing the descriptors Nutritional status, Elderly, Habits, Quality of life, Health promotion, Universities, including 25 articles in Portuguese language published in the period from 2010 to 2018. Regarding the nutritional profile, the largest portion was overweight, high consumption of energy foods and low consumption of foods that are sources of fiber, vitamins, calcium. The interventions carried out by most universities have shown positive results, helping to form good eating habits, improving the quality of life and promoting the health of the elderly. It was also verified, in most of the articles, that the students participating in these programs had arterial hypertension and due style, used medicines, in addition, they were married, with a good level of education and retired. In view of the results, it can be seen that the elderly who seek senior citizens’ universities are overweight, have diseases, such as hypertension, follow a lifestyle, and a highly lipidic diet, but low in fiber.